Hasil Belajar Siswa Ppkn Pada Materi Norma Kesopanan Melalui Metode Snowball Throwing Kelas VIII Di SMPN 2 Sumberasih - Rusdianto Adi Wijaya; Uswatun Hasanah; Didit Yulian Kasdriyanto (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The learning process with the conventional lecture model still does not give a deep impression to students. Teachers provide more explanations than finding out how far students can receive and understand the information conveyed. This problem then it is appropriate in teaching to do an innovation. In this case, teachers as educators must be able to use learning strategies that can attract students' attention to follow the lesson. This is the problem of this research is how Student Learning Outcomes Against the Snowball Throwing Cooperative Method which aims to find out how the Snowball Throwing learning method affects student learning outcomes. This research method uses a descriptive qualitative method. Data collection techniques in this study are by conducting observations, interviews, tests, and documentation. The results of the study using the Snowball Throwing learning model went quite well with several stages implemented by the teacher in learning activities, namely: the teacher explains the material being studied, the teacher divides students into 4 groups and orders the group leader to repeat the material, each group leader turns to their own group then repeats the material to their group, the teacher gives one worksheet to each group to record questions related to the material being studied, the paper will be formed into a ball and thrown to another group within 20 minutes, after which each group will get one ball of paper containing questions and the teacher gives each group a period of time to answer the questions then representatives from each group will present their results in front of the class until all groups have finished presenting their results.